2011
DOI: 10.1165/rcmb.2009-0288oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Synergizes Lipopolysaccharide-Induced InterIeukin-1β and Tumor Necrosis Factor–α Secretion from Macrophages via Substance P–Mediated Nuclear Factor–κB Activation

Abstract: A recent study has indicated that alveolar macrophages from smokers incubated with lipopolysaccharide (LPS) secrete much more IL-1b and TNF-a than those from healthy nonsmokers, but the mechanisms underlying this augmented secretion by cigarette smoke (CS) remain unknown. CS and LPS reportedly promote macrophages' secreting substance P (SP) that could up-regulate these cytokines' secretion from macrophages by acting on neurokinin 1 receptor (NK1R). Moreover, NF-kB from macrophages participates in NK1R intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Cigarette smoke contains many toxic components, including potentially bacterial lipopolysaccharides [56], which in combination with the delivered nicotine could contribute to these observed effects of cigarette smoke. HBD2 is expressed in keratinocytes, the gingival mucosa and the tracheal epithelium [48,57-59] and alteration of its gene expression has been found in many diseases, such as infectious diseases, CF, and lupus erythematosus [60]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke contains many toxic components, including potentially bacterial lipopolysaccharides [56], which in combination with the delivered nicotine could contribute to these observed effects of cigarette smoke. HBD2 is expressed in keratinocytes, the gingival mucosa and the tracheal epithelium [48,57-59] and alteration of its gene expression has been found in many diseases, such as infectious diseases, CF, and lupus erythematosus [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Xu recently showed that cigarette smoke extract significantly increased the production of IL-1β [57]. It was also shown that cigarette smoke inhibits the subsequent induction of hBD2 expression in response to bacterial lipopolysaccharide [52] or IL-1β [51], suggesting that cigarette smoke also may suppress the normal host defense response to bacterial pathogen exposure in the lung [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cigarette smoke has been shown to cause inflammatory responses in chronic smokers, and many in vitro studies have shown that treatment with TPM (cigarette smoke condensate) results in induction of several cytokine genes (Swenson et al, 2011) and secretion of cytokines Xu et al, 2011). We investigated whether the combustible and smokeless TPPs differ in their ability to induce cytokine secretion.…”
Section: Il8 Secretion Of Pbmcs Hl60 and Thp1 Cell Lines By Tpm Ws-mentioning
confidence: 99%
“…CS stimulated TLR4 signalling, increased caspase‐1 activity, IL‐1β and CXCL8 release from human bronchial epithelial cells via TLR and inflammasome activation . CS amplified IL‐1β and TNFα secretion of LPS‐TLR‐stimulated alveolar macrophages . Thus, smoking augments TLR‐triggered innate immunity and proinflammatory cytokine release.…”
Section: Aggravating Factors Of Hs Activate Inflammatory Monocyte–macmentioning
confidence: 95%